3 Efektivitas Dalam Pengawasan Asrama Sma Negeri Keberbakatan Olahraga Provinsi Bengkulu - Ayu, Puja Putri; Lorita, Evi; Handayani, Tuti; Sariningsih, Marida (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
This research aims to describe the Effectiveness in Supervision of SMANKO Dormitory in Bengkulu Province. The approach in this research uses a descriptive qualitative approach. Data collection techniques were conducted by interview and documentation. Data analysis techniques used include data reduction, data presentation (data display) and conclusion drawing/verification. The results showed that, from the results of interviews and discussions about "Effectiveness in the Supervision of SMANKO Dormitory in Bengkulu Province" it can be concluded that the effectiveness in the supervision of SMANKO dormitory has been running quite well, which is seen based on the indicators of the theory of six effective leadership traits according to Edwin Ghiselli in Usman Effendi (2014: 186) namely, supervisory ability, technical knowledge, decisiveness, self-confidence and initiative. Of the six indicators, there are two indicators that still need to be improved, namely, supervisory ability, there is still a lack of supervision of the dormitory caregivers on the afternoon and night shifts because it is far from supervising the dormitory coordinator's working hours so that it is vulnerable to caregivers who are not there at that time and technical knowledge (intelligence) still lacks a match for the educational background of some dormitory caregivers.